(untitled) (Literary Voice, 2024)
“Men are more likely than women to be given medication when they report pain to their doctors. Women are more likely to be given sedatives,” claims Leslie Jamison while citing evidence from the 2001 study The Girl Who Cried Pain (Jamison 117). Pain as an experiential category is different from other somatic experiences, in that it is heavily dependent not only on its mitigation but also on its avowal of external perceptual forces. As Elaine Scarry puts it “To have great pain is to have certainty; to hear that another person has pain is to have doubt” (Scarry 7). This is true except in circumstances when one is inflicting pain on another – such as torture, where the other’s articulation of pain reinforces the effectiveness of pain being inflicted. A close look at the existing theoretical apparatus and literary representations of women’s physical pain reveals a big issue. Even when gender is acknowledged as a contributing factor in women’s pain, these conversations are often limited to representations of descriptions of sexual assault, childbirth and, fairly recently, menstruation. The experiences of female pain that aren’t solely mediated through the genitalia, lack both representation and a theoretical vocabulary to talk about them productively. My engagement with pain as a symptom of lupus shows that there are experiences of pain heavily dependent on gender identity, which have nothing to do with the genitalia. In establishing a theoretical apparatus for talking about such experiences it might be useful to draw on Flannery O’Connor’s letters as a test for the theoretical apparatus thus developed.